2014
DOI: 10.3109/19401736.2014.971239
|View full text |Cite
|
Sign up to set email alerts
|

Probing the phylogenetic relationships of a few newly recorded intertidal zoanthids of Gujarat coast (India) with mt DNA COI sequences

Abstract: The present study reports the phylogenetic relationship of six zoanthid species belonging to three genera, Isaurus, Palythoa, and Zoanthus identified using systematic computational analysis of mtDNA gene sequences. All six species are first recorded from the coasts of Kathiawar Peninsula, India. Genus: Isaurus is represented by Isaurus tuberculatus, genus Zoanthus is represented by Zoanthus kuroshio and Zoanthus sansibaricus, while genus Palythoa is represented by Palythoa tuberculosa, P. sp. JVK-2006 and Paly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies describing the occurrence of zoantharian along the coast of the Indian subcontinent were carried out by Hornell (1910), Bhattiji (2010), Kaladhran et al (2011), Pandya et al (2013 and Trivedi et al (2014). Based on mt DNA COI sequences, the phylogentic relationship of zoantharians was studied by Joseph et al (2014) who reported the occurrence of 6 species from the Kathiawar Peninsula. Kumari et al (2015) studied the distribution pattern and community structure of 7 different species of zoantharians in 3differ-ent genera (Isaurus, Palythoa, and Zoanthus) along the Saurashtra coast.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…Studies describing the occurrence of zoantharian along the coast of the Indian subcontinent were carried out by Hornell (1910), Bhattiji (2010), Kaladhran et al (2011), Pandya et al (2013 and Trivedi et al (2014). Based on mt DNA COI sequences, the phylogentic relationship of zoantharians was studied by Joseph et al (2014) who reported the occurrence of 6 species from the Kathiawar Peninsula. Kumari et al (2015) studied the distribution pattern and community structure of 7 different species of zoantharians in 3differ-ent genera (Isaurus, Palythoa, and Zoanthus) along the Saurashtra coast.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%
“…The study demonstrated the existence of six haplotypes of C. karachiensis with phenotypic plasticity in the study region, suggesting initiation of the speciation. Phylogenetic analysis byJoseph et al (2016a) proved efficacy of COI gene in distinguishing six zoanthid species from the Saurashtra coast. Detailed taxonomic investigation of a new polychaete species Heterospio indica from NWI coast byParapar et al (2016) was complemented with molecular analysis where 18S and COI genes were deposited in GenBank and represented the first sequencing of the species of Heterospio belonging to monogeneric family Longosomatidae Rengaiyan and Ingole (2018).…”
mentioning
confidence: 96%